Effect of high thermal stress on the organic light emitting diodes (OLEDs) performances - Mohammad, Muhammad Azrain; Mansor, Muhd Ridzuan; Omar, Ghazali; Sheikh Md Fadzullah, Siti Hajar; Dhar Malingam, Sivakumar; Nordin, Mohd Nur Azmi; Esa, Siti Rahmah (Elsevier B.V., 2019)
The configuration of an organic light emitting diode (OLED) that combines different types of material to form a complete, functional device has induced an interlayer stress. This situation can further affect the performances of OLED, especially under high-temperature conditions as regards to different values of the thermal expansion coefficient (CTE) between the layers. Hence, this paper presents the thermal behavior of OLEDs under such conditions specifically in non-operated mode (no electrical current is given during the experiment). A batch of commercially available OLEDs has been employed. They were exposed to several temperatures in a controlled oven, including temperatures that higher than the glass transition temperature (Tg) limit of the polymer material (∼126 ℃). It was observed that the luminance value had dramatically dropped by 90% from the initial value after the OLEDs were stressed at 135 ℃, whereas the voltage-drop greatly escalated from 8.5 V to 30.2 V. Via FIB-FESEM analysis, the presence of voids (layer mismatch) was evident due to interfacial thermal stress imparted between the layers. The voids had allowed the infiltration of moisture and oxygen into the device and eventually led to the formation of bubble-like defects on top of the cathode’s surface. This condition has resulted in deterioration of electrons injection path and permanently changed the morphological structures of the devices. Through calculations, it was verified that the interfacial thermal stress between the layers reduced about 50% as the thickness of the polymer layer was increased by two times of its initial dimension.